Comment on Zwally and others (2015)-mass gains of the Antarctic ice sheet exceed losses - Richter, Andreas Jorg; Horwath, M.; Dietrich, R. (Journal of Glaciology)
In their article ‘Mass gains of the Antarctic ice sheet exceed losses’ Zwally and others (2015) choose Vostok Subglacial Lake as an exemplary region to demonstrate their inference of surface height change rates from a portion of the ICESat mission’s laser altimetry data (2003–08). In their appendix, they discuss some of the remarkable differences between their results and those reported by Richter and others (2008, 2013, 2014). However, the selective consideration of our works and the misleading or incorrect interpretation of our results call for clarification Fil: Richter, Andreas Jorg. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Technische Universitaet Dresden; Alemania Fil: Horwath, M. Technische Universitaet Dresden; Alemania Fil: Dietrich, R. Technische Universitaet Dresden; Alemania